Effects of chemical reactions in the presence of temperature variations and isothermal mass diffusion over an inclined plate - Nagarajan, Gnanavel; Sundar Raj, M.; Venkayesan, J.; Jeyanthi, L.; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
A detailed study of the erratic circulation around an unbounded inclined plate under fluctuating temperature and isothermal mass dispersion was carried out with a chemical reaction. This work concentrated on the harmonic inclination of the plate in its plane, and the accurate solution of the non-dimensional governing formulations was made possible by the Laplace transform technique. To evaluate their impact on different profiles, the investigation examined a variety of physical factors, including phase inclination, chemical response variable, Schmidt number, thermal Grashof number, mass Grashof number, and duration. Notably, the speed per second increased with decreasing phase angle. Furthermore, a decrease in either the thermal radiation variable or the chemical response variable induced an increase in velocity.
Keywords: tilted surface; thermal transfer; mass transmission